Inv dup (15) with mental retardation but few dysmorphic features. Issue 3 (June 1984) - Gilmore, D H; Boyd, E; McClure, J P; Batstone, P; Connor, J M
Abstract : We report a Scottish child with inv dup (15) and compare the clinical features with those of previously reported cases. Since the first report by Parker and Alfi in 1972, there have been 44 reports of patients with confirmed or suspected inv dup (15). The extra chromosomal material has been variously described, but in all cases there appears to be an additional G group sized chromosome in which both ends are derived from the short arm, centromere, and proximal long arm of chromosome 15. In most cases there are satellites at both ends of this extra chromosome. We report the first patient from Scotland with similar cytogenetic findings.